REDESIGNING THE CYCLONE SEPARATOR EXPANSION TO MAXIMIZE PROCESS EFFICIENCY - Bankova, Aleksandrina (Innovation in Woodworking Industry and Engineering design, 2024)
The paper examines the specific characteristics considered when determining the amount of sheet material necessary for the manufacture of machine parts with a predominant number of sheet material components. Pointed out is the possibility to optimize material consumption at the stage of design by incorporating the capabilities of AutoCAD software. Research conducted revealed that the quantity of material with a predominant number of sheet material components, such as a cyclone separator, is increasingly subject to the accuracy of cutting and positioning of workpiece unfolding on the sheet material, which is ultimately related to the increased process optimization.